A decisão do investimento pós-keynesiana: teoria e aplicação - Aidar, Gabriela Lima (2019)
The purpose of this thesis is to present a proposal of a post-Keynesian investment theory, which contributes to the heterodox microeconomics, especially for the post-keynesian one,which is still incipient. In this respect, Keynes´ oeuvre show the key role of the entrepreneur on the macroeconomic dynamics, since she is responsible for the decision of investment, the fundamental element to generate employment and income. This allows for a microeconomic view of the Post Keynesian theory, especially of the investment decision-making, which justifies this research. The theoretical proposal of the thesis is tested in empirical analysis of companies listed in the São Paulo Stock Market; the empirical exams test the firms both jointly and individually. In the analysis of the set of companies, panel data methods of Ordinary Least Squares, Fixed Effect and Random Effect and Generalized Method of Moments were used. The main results pointed to the lagged long-term investment, long-term loan and Long-Term Interest Rate as significant variables to explain the investment decision.When analyzing individual companies, Ordinary Least Squares, Generalized Method of Momentsand Autorregressive Distributed Lagtime series methods were employed. In this second analysis, making use of Ordinary Least Squares and Generalized Method of Moments we highlight the lagged long-term investment, long-term loan and Marginal Capital Efficiency with significantive results in accordance with the theoretical proposal; while with Autorregressive Distributed Lagtime models, the Long-Term Interest Rate and Marginal Efficiency of Capital were significative, whereas the companies Ultrapar and Lojas Americanas present all variables as significantive to explain the long-term investment.The use of various econometric methods aims at making theempirical exams more robust and able to furnish support to the theoretical proposal of the investment decision-making.